1947
DOI: 10.1038/bjc.1947.34
|View full text |Cite
|
Sign up to set email alerts
|

Serial Transmission of Infectious Papillomatosis in the Domestic Rabbit

Abstract: IN a previous communication a description was given of the lesions that occurred in rabbits when the same area of skin was inoculated by scarification with a suspension of glycerolated Shope papillomas from a cottontail rabbit and a suspension of sheep dermatitis lesions (Selbie, 1946). It was observed that the two infections had a suppressing or interfering effect on each other, and that the magnitude of this effect depended on the timing of the inoculation of the two infective suspensions. The most important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1954
1954
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…CRPV vegetative DNA replication, late transcripts, and capsid antigens are seldom detected in domestic rabbit warts (37,41,62). CRPV strains recoverable from domestic rabbit warts have been reported, however (18,50,52), suggesting a genetic heterogeneity of the virus. This prompted us to compare the FIG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CRPV vegetative DNA replication, late transcripts, and capsid antigens are seldom detected in domestic rabbit warts (37,41,62). CRPV strains recoverable from domestic rabbit warts have been reported, however (18,50,52), suggesting a genetic heterogeneity of the virus. This prompted us to compare the FIG.…”
Section: Resultsmentioning
confidence: 99%
“…Warts of naturally infected cottontail rabbits usually contain large amounts of virions, in spite of a great variation in virus content observed among rabbits (3). In contrast, little, if any, infectious virus is recovered from domestic rabbit warts (3, 18, 51, 52), and vegetative viral DNA replication, late transcripts encoding L1 and L2 capsid proteins, and capsid antigens are seldom detected (35,37,41,62).The first evidence for a biological variation of CRPV has been the isolation of strains recoverable from domestic rabbit warts (18,50,52). The existence of cancer-producing variants was proposed to account for tumor progression (44) but could not be substantiated (43,45,53).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Papillomas, primary carcinomas, and metastases from domestic European rabbits have about 10-100 copies of viral DNA, whereas papillomas from Sylvilagus rabbits have 2400-8800 copies (Stevens and Wettstein, 1979). Papillomas from domestic European rabbits can be serially transferred, but only small amounts of infectious virus are typically demonstrated (Gross, 1983;Hu et al, 2007;Selbie and Robinson, 1947;Shope, 1935), indicating that domestic European rabbits are not a source of virus for arthropod vectors.…”
Section: Epidemiologymentioning
confidence: 99%
“…In earlier studies, investigators achieved very limited success in passaging virus in domestic rabbits (Shope, 1935;Friedewald & Kidd, 1944). Further study suggested that CRPV infection produced masking viruses which was interpreted as immature particles located in the infected cell nuclei of domestic rabbit papillomas (Selbie & Robinson, 1947;Ito & Evans, 1961;Evans et al, 1964;Evans & Rashad, 1967). However, because of limited reagents for the detection of virus proteins, especially late protein L1 and L2, it was not clear whether CRPV infection in domestic rabbit led to expression of L1 and infectious virions.…”
Section: Introductionmentioning
confidence: 99%